KEMAMPUAN KOMUNIKASI MATEMATIS DIKAJI DARI SELF-ESTEEM SISWA PADA MATERI HIMPUNAN - Dina Elviani; Sugiatno Sugiatno; Silvia Sayu (Jurnal AlphaEuclidEdu, 2020)
This study aims to find out how students' mathematical communication skills in solving sets of questions that have high, medium, and low self-esteem, in class VII of SMP Islam Bawari in Pontianak. This study used a descriptive qualitative research method with a survey form. The subjects of this research is 29 students in class VIIB SMP Islam Bawari Pontianak. Test and non-test techniques are used in this study as data collection techniques. Self-esteem questionnaire test, mathematical communication ability test, and interview are the tools used in this research. The results of this study are students with a high level of self-esteem that have fulfilled the category of mathematical communication skills, including that students are relatively able to understand the context of the problem in presenting the information obtained from the problem; Students with moderate levels of self-esteem almost meet the category of mathematical communication skills, This is indicate that students have a difficulty in solving problems, so the answers given are incomplete and inaccurate with the information contained in the questions; Students with low levels of self-esteem barely meet the category of communication skills, This is indicate that students have a difficult in understanding the purpose of the question.Keywords: Material of Set, Mathematical Communication Skills, Self-Esteem